Aryl Radical Formation by Copper(I) Photocatalyzed Reduction of Diaryliodonium Salts: NMR Evidence for a CuII/CuI Mechanism. Issue 33 (2nd July 2013) - Baralle, Alexandre; Fensterbank, Louis; Goddard, Jean‐Philippe; Ollivier, Cyril
<x xml:space="preserve">Abstract</x> Photocatalyzed reduction of diaryliodonium salts was achieved by using [Cu(dpp)2][PF6] as a photoactive complex and DIPEA as a reductive quench. The application of a copper catalyst allows the generation of aryl radicals under mild conditions and maintains their reactivity for CC bond formation processes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>